Study of structural and electronic properties of GaSb:V - Yaringaño, Roxani (2021)
Gallium antimonide binary semiconductor has had many applications in optoelectronic devices in recent years. The study of their defects in semiconductor materials is of vital interest for this type of application. But, in addition to the routine characterization of the undoped semiconductor, it is necessary to characterize the effects produced by electrically active impurities in the doped samples. In this work, the structural and electronic properties of the vanadium doped gallium antimonide binary semiconductor (GaSb: V) were studied by means of an Atomic Force Microscope. The scan of its surface was carried out in the tapping mode to obtain images of the topography and topographic profiles of the sample, while the electronic properties were determined through the I vs V curves obtained by the contact mode.